The Implications of South African Economic Growth for the Rest of Africa - Arora, Vivek (IMF Working Papers; Working Paper ;, 2005)
This paper measures the extent to which South African economic growth is an engine of growth in sub-Saharan Africa. Results based on panel data estimation for 47 African countries over four decades suggest that South African growth has a substantial positive impact on growth in the rest of Africa, even after controlling for other growth determinants. The estimates are robust to the effects of global and regional shocks, changes in model specification, and sample period.